Macrophages assemble! But do they need IL‐4R during schistosomiasis?. Issue 7 (3rd July 2019) - Rückerl, Dominik; Cook, Peter C.
Abstract: Helminth infections are a global health burden in humans and livestock and are considered to be a major evolutionary driver of type 2 immunity (orchestrated by type 2 cytokines, e.g., IL‐4 and IL‐13). Upon infection, helminths cause substantial damage to mucosal tissues as they migrate within the host and elicit crucial protective immune mechanisms. Macrophages, essential innate cells, are known to adopt a specific activation status (termed M(IL‐4)) in type 2 cytokine environments. Yet, the role of these macrophages in mediating protective immune/wound healing responses to helminths is unclear. Furthermore, macrophage subsets can be very heterogenous (linked to their differing cellular origins) and the relative role of these subsets in the context of M(IL‐4) activation to helminth infection is unknown. An article by Rolot et al . in this issue of the European Journal of Immunology [Eur. J. Immunol. 2019. 49: 1067–1081] uses a variety of transgenic murine strains to revise our understanding of the complexity of how these subsets undergo M(IL‐4) activation and participate in wound healing responses in helminth infection. Here we highlight that consideration of different macrophage subsets in mucosal tissues is essential when evaluating the functional role of M(IL‐4) macrophages.